Activin A: its role and involvement in inflammatory diseases - Tie, Tung Hing; Basir, Rusliza; Chuah, Yaw Kuang; Talib, Herni; Nordin, Norshariza (Universiti Putra Malaysia Press, 2015)
Activin proteins are members of the transforming growth factor-β family. Activin A is involved in several biological responses including wound repair, cell death, proliferation and differentiation of many cell types. Biologically active activins consist of homodimers or heterodimers of two beta (β) subunits that are linked together by a single covalent disulphide bond. The subunits in humans are βA, βB, βC and βE. As an example, a combination of two βA subunits will produce a unit of activin A. These proteins are found in most cells of body such as macrophage and activated circulating monocytes. Their role in inflammation can be categorised into two types, either pro- or anti-inflammatory agents, depending on the cell type and phase. Activin signals are kept in balance by antagonist follistatin (Fst), which is a glycoprotein expressed in tissues and encoded by the follistatin gene in humans.